Exploring the Role of Consumer Satisfaction in Online Herbal Skincare Purchases - Agustin, Ayu; Yuniasanti, Reny (Psikostudia : Jurnal Psikologi, 2026)
The development of digital technology has brought significant changes in consumer behavior worldwide, including in Indonesia. E-commerce, as one of the main digital platforms, has transformed the way consumers shop, offering greater convenience, effectiveness, and personalization. This phenomenon is reflected in the increasing demand for herbal skincare products, which are becoming more popular among consumers. Along with this behavioral shift, understanding the factors that influence purchasing decisions is crucial for business development, especially in the online market. This study aims to analyze the relationship of consumer satisfaction on purchase decisions for herbal skincare products purchased online. This research uses a quantitative approach with a correlational design. The research population consists of consumers who purchase herbal skincare products online, with a sample of 100 respondents selected using purposive sampling. Data was collected using a Likert scale to measure consumer satisfaction and purchase decisions. The results show that consumer satisfaction significantly influences purchase decisions, with most respondents falling into the medium satisfaction category. External factors such as brand loyalty and social media influence also play a role in purchase decisions. This study suggests that businesses should focus on improving consumer satisfaction through product quality and an enjoyable shopping experience, while also considering external factors such as promotions and recommendations from other consumers to enhance purchase decisions.